(untitled) (Fiep Bulletin - online, 2015)
The objective of the study is to analyze the results obtained in performance tests with Elementary School students from the Municipal Education Network of Vitória/Espírito Santo, and to compare the relationship between anthropometric measure and result attained in the motor tests. A total of 49 students ranging from 12 to 13.6 years of age were tested, consisting of 23 males and 26 females. The tests applied were: 50-meter flat race, 600 meters, standing long jump (SDP) and running jump (SDV) and high jump (S). The students submitted to the measurement of the vertex height, pursuant to (DE ROSE, 1984) and of the Total Body Mass (MC). The students were distributed in two groups, one of males and one females, and were divided up into three subgroups, (Y), (x) and (Z). The mean results of each test and parameter were obtained after distribution between the subgroups, aiming at comparison for conclusions. X=X/N, from Stevenson (1981), was used to obtain the mean results. It was concluded that male students from group 1 achieved the best results. A fact that we did not identify in the female groups, where the results were divided among the three groups.